Services Quality and Hotel System are an Important Determinant for the Customers’ Satisfaction Towards Customers’ Loyalty for EDC Hotel in North State of Malaysia - Haderi, Sami AL; Arussi, Ali AL; Ismail, Waddah; Sanabani, Tawfik Al; Hamdani, Adel AL (International Journal of Engineering and Technology, 2018)
The study purposes to investigate consistency in previous literacy regarding Services Quality and Hotel System influencing the customers’ loyalty throughout the customers’ satisfaction for EDC Hotel Malaysia. Also, this paper aims to identify areas for service improvement by providing more explanation for these factors affecting customers’ satisfaction comparing to the previous researches in this area. The methodology used in the study was survey questionnaire was distributed to 300 respondents, the sample size was 231 respondents which ready for analysis and the sample technique was convenience sample sampling.  A non-parametric test using analysis of variance (ANOVA) to analysis satisfaction scores of respondents using SPSS 24TH. The results of the study found that on average, respondents were quite satisfied with hotel services. Also, hotel system effect on customer’s satisfaction directly. Also, the result revealed that components of service’s quality provided by hotel were the main differences in the results were provided by the previous researches. The mean significant of the study is to conduct customer’  satisfaction  surveys  as  a tool for identifying  areas  for  service’s improvements  and  ensuring  that  it  remains  responsive to help  in  justifying resources and improving the services. Hence, there is a need for hotel management to understand the customer needs and satisfy these needs. In order to support in an ongoing services providing. The study provides literature on customers’ loyalty and satisfaction.